2010
DOI: 10.1096/fj.09-152678
|View full text |Cite
|
Sign up to set email alerts
|

An animal model of spontaneous metabolic syndrome: Nile grass rat

Abstract: Metabolic syndrome (MetS) is a prevalent and complex disease, characterized by the variable coexistence of obesity, dyslipidemia, hyperinsulinaemia, and hypertension. The alarming rise in the prevalence of metabolic disorders makes it imperative to innovate preventive or therapeutic measures for MetS and its complications. However, the elucidation of the pathogenesis of MetS has been hampered by the lack of realistic models. For example, the existing animal models of MetS, i.e., genetically engineered rodents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 33 publications
(37 reference statements)
3
66
0
4
Order By: Relevance
“…Previous work had established that male Nile rats exhibit many features of metabolic syndrome, including hypertension, hyperlipidemia, and hyperglycemia which proceeded to overt diabetes by approximately 6 months (Chaabo et al 2010, Noda et al 2010, Bolsinger et al 2013. FBG values above 5.6 mmol/L (100 mg/dL) were considered hyperglycemic based on clinical criteria for metabolic syndrome in humans (Alberti et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work had established that male Nile rats exhibit many features of metabolic syndrome, including hypertension, hyperlipidemia, and hyperglycemia which proceeded to overt diabetes by approximately 6 months (Chaabo et al 2010, Noda et al 2010, Bolsinger et al 2013. FBG values above 5.6 mmol/L (100 mg/dL) were considered hyperglycemic based on clinical criteria for metabolic syndrome in humans (Alberti et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared the effects of feeding a highcalorie, lowfiber (chow) diet of a type known to induce diabetes in Nile rats (Chaabo et al 2010, Noda et al 2010) with a highfiber (Hfib) control diet that more closely resembles the Nile rats' native diet. Comparison of the two groups until 12 months showed that a highfiber diet alone was effective in reducing the incidence of hyperglycemia from 83 to 0%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nile grass rat (NGR), Arvicanthis niloticus, is a herbivorous rodent inhabiting dry savanna, woodlands, and grasslands in Africa. Noda and colleagues [138] recently showed that the NGR is a precious, spontaneous model for exploring the etiology and pathophysiology of MetS as well as its various complications.…”
Section: Spontaneous Animal Models Of Lipoprotein Disordersmentioning
confidence: 99%